Does self-employment reduce unemployment? - David B. Audretsch; Martin A. Carree; André J. van Stel; A. Roy Thurik (Max Planck Institute for Research into Economic Systems, 2005)
This paper investigates the dynamic interrelationship between self-employment and unemployment rates. On the one hand, unemployment rates may stimulate start-up activity of self-employed. On the other hand, higher rates of self-employment may indicate increased entrepreneurial activity reducing unemployment in subsequent periods. These two effects have resulted in considerable ambiguities about the interrelationship between unemployment and entrepreneurial activity. This paper introduces a two-equation vector autoregression model capable of reconciling these ambiguities and tests it for data of 23 OECD countries over the period 1974-2002. The empirical results confirm the two distinct relationships between unemploy-ment and self-employment, i.e. "refugee" and "entrepreneurial" effects. We also find that the "entrepreneu-rial" effects are considerably stronger than the "refugee" effects.
More recent version: http://hdl.handle.net/10419/110993
Keywords: M13; L11; 330; entrepreneurship; Gibrat's Law; self-employment; unemployment; Selbstständige; Beschäftigungseffekt; Arbeitslosigkeit; VAR-Modell; OECD-Staaten